Disease Severity and Prognosis of SARS-CoV-2 Infection in Hospitalized Patients Is Not Associated With Viral Load in Nasopharyngeal Swab - Cocconcelli, Elisabetta; Castelli, Gioele; Onelia, Francesco; Lavezzo, Enrico; Giraudo, Chiara; Bernardinello, Nicol; Fichera, Giulia; Leoni, Davide; Trevenzoli, Marco; Saetta, Marina; Cattelan, Annamaria; Crisanti, Andrea; et al. (Frontiers in Medicine, 2021)
Background: The impact of viral burden on severity and prognosis of patients hospitalized for Coronavirus Disease 2019 (COVID-19) is still a matter of debate due to controversial results. Herein, we sought to assess viral load in the nasopharyngeal swab and its association with severity score indexes and prognostic parameters. Methods: We included 127 symptomatic patients and 21 asymptomatic subjects with a diagnosis of SARS-CoV-2 infection obtained by reverse transcription polymerase chain reaction and presence of cycle threshold. According to the level of care needed during hospitalization, the population was categorized as high-intensity (HIMC, n = 76) or low intensity medical care setting (LIMC, n = 51). Results: Viral load did not differ among asymptomatic, LIMC, and HIMC SARS-CoV-2 positive patients [4.4 (2.9–5.3) vs. 4.8 (3.6–6.1) vs. 4.6 (3.9–5.7) log10 copies/ml, respectively; p = 0.31]. Similar results were observed when asymptomatic individuals were compared to hospitalized patients [4.4 (2.9–5.3) vs. 4.68 (3.8–5.9) log10 copies/ml; p = 0.13]. When the study population was divided in High (HVL, n = 64) and Low Viral Load (LVL, n = 63) group no differences were observed in disease severity at diagnosis. Furthermore, LVL and HVL groups did not differ with regard to duration of hospital stay, number of bacterial co-infections, need for high-intensity medical care and number of deaths. The viral load was not an independent risk factor for HIMC in an adjusted multivariate regression model (OR: 1.59; 95% CI: 0.46–5.55, p = 0.46). Conclusions: Viral load at diagnosis is similar in asymptomatic and hospitalized patients and is not associated with either worse outcomes during hospitalization. SARS CoV-2 viral load might not be the right tool to assist clinicians in risk-stratifying hospitalized patients.